ANALISIS KONSINYASI TITIPAN UANG DI PENGADILAN NEGERI SEBAGAI BENTUK PENYELESAIAN GANTI KERUGIAN PEMBEBASAN LAHAN JALAN TOL SUMATERA DI PENGADILAN NEGERI KALIANDA - Dilla Nandya Oksitania; Erlina B; Yulia Hesti (Fakultas Hukum Universitas Tulang Bawang, 2021)
Abstract Land is the most important element for humans to be able to live, this is because it is where natural and man-made resources grow and are also built. Indonesia regulates land ownership through this land law so that land use or management can be carried out carefully now and in the future. The land issue concerns the most basic rights of the people. The purpose of the study was to determine the consignment process in the District Court as a form of settlement of compensation for toll road land acquisition and its legal consequences. The results showed that the consignment process for compensation began with an application for consignment safekeeping, then an offer was made by the court bailiff accompanied by 2 (two) witnesses at the respondent's residence. The consignment waives the obligation as the debtor, because the consignment can be equated with making payments. All processes must be carried out in a manner that has been regulated by laws and regulations. Consignment is carried out so that government projects continue to run, through a deliberation mechanism that should be a means to find a middle way in determining the amount of compensation, often no agreement is reached. Keywords : Sumatra Toll Road, Consignment, Land Acquisition.